Supercritical Fluid Extraction of Emulsion-Assisted Encapsulation of Hypocholesterolemic Bioactive Compounds - Romero-Figueroa, J; Rojas-Sepulveda, A; Torres-Mediano, A; Cerro-Munoz, D; Matiacevich, S (Elsevier B.V., 2024)
β-sitosterol and Curcumin, known for their hypocholesterolemic effects, have difficulties for application in aqueous foods due to their reduced water solubility and stability. The encapsulation technique allows these compounds to be protected, resulting in increased bioavailability and bioaccessibility. This study investigated the feasibility of producing capsules using different biopolymeric coating materials through a Supercritical Fluids Extraction of Emulsions (SFEE) encapsulation process. Emulsions with homogeneous droplet sizes were processed at 40 [°C] by the SFEE method at pressures of 9 and 13 [MPa]. β-sitosterol powder was successfully encapsulated in both polycaprolactone and modified-starch matrices. Curcumin could only be encapsulated in modified starch, probably because of the highly hydrophobic nature of this compound. The resulting powders, with process efficiencies higher than 60%, were characterized by thermal, structural and morphological analyses, indicating agglomerated spherical capsules. Optimal encapsulation was at 9 [MPa] due to smaller capsule sizes, lower pressure requirements and reduced CO2 consumption. © 2024 Elsevier B.V.